Apakah Perencanaan Keuangan Berpengaruh Terhadap Kesejahteraan Keluarga Muslim Indonesia? - Risna Putri, Chikita Dinda; Saleh, Samsubar; Wardhana, Leo Indra (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
Welfare is the main goal in Maqashid Syariah where welfare is a person's release from poverty which must immediately get a solution, one of them is by doing financial planning The purpose of this study is to determine the effect of insurance, savings/investment, and pension funds on the consumption of household expenditures. This study was use Indonesian Family Life Survey data in the period of 2007 and 2014 using the panel data regression analysis method. The research results found that insurance has a significant influence on household expenditure consumption, savings/investments have a negative and significant influence on household expenditure consumption, pension funds have a negative and significant influence on household expenditure consumption.